New results from GridPix Detectors. (April 2020) - Bilevych, Y; Desch, K; Fransen, J-P; Van Der Graaf, H; Gruber, M; Hartjes, F; Van Der Heijden, B; Heijhoff, K; Ietswaard, C; John, D; Kaminski, J; Kluit, P; et al.
Abstract: GridPix structures combine the high resolution of a pixel readout chip with a Micromegas as gas amplification stage. This detector has shown excellent performance before with the Timepix ASIC, but has been improved by using the successor ASIC, the Timepix3. This new version of the GridPix detectors has been used in test beams at the ELSA accelerator at Bonn, where 2.5 GeV electrons are available for tracking studies. It could be demonstrated that the spatial resolution in both transverse and longitudinal direction follows the diffusion function. Structures made of four GridPixes have been designed and constructed to cover larger areas. Also these devices called quads have been successfully tested with the electron beam giving similarly good results as the single GridPix detector.